Simultaneous RP HPLC Determination of Aceclofenac, Paracetamol and Tizanidine in Pharmaceutical Preparations - V. V. Vaidya; G. R. Singh; M. P. Choukekar; M. B. Kekare (E-Journal of Chemistry)
A simple, fast and precise reverse phase high performance liquid chromatographic method is developed for the simultaneous determination of aceclofenac, paracetamol and tizanidine. Chromatographic separation of the three drugs were performed on a hypersil C18 column (250 mm x 4.6 mm, 5 µm) as stationary phase with a mobile phase comprising of mix phosphate buffer pH 7.0: acetonitrile (40:60 v/v), at a flow rate of 0.7 mL min-1 and UV detection at 230 nm. The proposed method was validated for linearity, accuracy, precision, LOD, LOQ. Linearity, accuracy and precision were found to be acceptable over the ranges of 100-300 µg mL-1 for aceclofenac, 500-1500 µg mL-1 for paracetamol and 2-6 µg mL-1 for tizanidine HCl equivalent to tizanidine. It can be conveniently adopted for routine quality control analysis.